Evaluation of gingival crevicular fluid cyclophilin a and extracellular matrix metalloproteinase inducer levels in different periodontal diseases. (August 2016) - Eren, Gülnihal; Türkoğlu, Oya; Atmaca, Harika; Atilla, Gül
Highlights: CypA is released extracellularly in response to inflammatory stimuli. CypA is able to regulate inflammatory responses via interaction with EMMPRIN. We showed that GCF CypA total amount was higher in G-AgP group. This result might suggest that this molecule is associated with G-AgP. Abstract: Objective: Cyclophilin A (CypA) is able to regulate inflammatory responses and matrix metalloproteinase production via its interaction with extracellular matrix metalloproteinase inducer (EMMPRIN). EMMPRIN is the cell surface receptor of CypA. The aim of the present study was to evaluate the gingival crevicular fluid (GCF) CypA and EMMPRIN levels in patients with chronic periodontitis (CP), generalized aggressive periodontitis (G-AgP) and periodontally healthy controls. Methods: Twenty CP patients, 19 G-AgP patients and 20 healthy control subjects were included in the present study. All study participants were non-smokers. Full mouth clinical periodontal parameters including probing depth, clinical attachment level, plaque index, and papilla bleeding index were recorded. GCF CypA and EMMPRIN levels were analyzed by enzyme-linked immunosorbent assay. Data were analyzed statistically with parametric and non-parametric tests. Results: GCF CypA total amount was higher in the G-AgP group compared to healthy controls (p < 0.05), whereas CypA total amounts were similar in CP and healthy controls (p > 0.05). No significant difference in GCF CypA total amount between CP and G-AgP was observed (p > 0.05). Also, there was no significant difference in GCF EMMPRIN total amounts among the study groups (p > 0.05). Conclusion: Higher levels of GCF CypA in patients with G-AgP might demonstrate that CypA is associated with the inflammatory infiltrate and alveolar bone destruction of G-AgP. However, GCF CypA level does not seem to be affected by CP. Similar GCF EMMPRIN levels in diseased and healthy groups might suggest that EMMPRIN has role in the turn over of connective tissues in physiological conditions as well as pathological state.